Amphiphilic Low-Molecular-Weight Gelators Bearing β-S-N-Acetylglucosamine Linked to a Tartaric Acid Scaffold: Synthesis, Self-Assembly and Wheat Germ Agglutinin Binding - Peña Garcia, Vicente Leafar (2023)
The self-assembly of carbohydrate-based amphiphiles can lead to colloidal soft materials such as supramolecular gels featuring highly desirable characteristics like biodegradability and biocompatibility. The report herein presents the synthesis, characterization and supramolecular self-assembly, physical gelation and wheat lectin binding of two structurally related amphiphilic compounds having β-S-N-acetylglucosamine residues linked to a 2,3-diacyl-N,N′-dipropargylated-l-tartaric diamide. A 1-thio-β-N-acetyl-d-glucosamine precursor attached to a conveniently functionalized linker with an azido group was synthesized by means of a one-pot procedure followed by deprotection. A click reaction successfully led to the two amphiphiles, which differed in length of the fatty acid attached to the tartaric acid scaffold. Although both compounds are poorly soluble in water and organic solvents, the difference in terms of hydrophilic moieties provided them with distinct supramolecular gelation properties. While the presence of an octadecyl chain produced a hydrogelator, the dodecadecyl homologue would only form weak gels in DMSO. SEM and rheology experiments confirmed the characteristic fibrillar morphology and viscoelastic properties, in agreement with the presence of physical gels. Both amphiphiles were able to interact reversibly with wheat germ agglutinin (WGA), a lectin that specifically recognizes GlcNAc residues, indicating a potential use in the food industry, as a gluten sensitivity manager, as well as in health-related industries, for example, for drug delivery systems.